2009
DOI: 10.1007/978-1-60761-380-0_27
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Epithelial Stem Cells In Vivo and In Vitro Using Keratin 19 and BrdU

Abstract: Progress in the identification of skin stem cells and the improvement of culture methods open the possibility to use stem cells in regenerative medicine. Based on their quiescent nature, the development of label retention assays allowed the localization of skin stem cells in the bulge region of the pilosebaceous units and in the bottom of rete ridges in glabrous skin. The development of markers such as keratin 19 also permits their study in human tissues. In this chapter, protocols to identify skin stem cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…The lack of immunoreactivity demonstrated that these keratinocytes actually lacked the CK19 antigen; CK19 is considered to be a putative stem cell marker, and it is only expressed in the most basal layer, which might relate to the local environments that penetrate the basement membrane (Larouche et al, 2005;Larouche et al, 2010;Michel et al, 1996).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…The lack of immunoreactivity demonstrated that these keratinocytes actually lacked the CK19 antigen; CK19 is considered to be a putative stem cell marker, and it is only expressed in the most basal layer, which might relate to the local environments that penetrate the basement membrane (Larouche et al, 2005;Larouche et al, 2010;Michel et al, 1996).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…Nevertheless, both studies showed the presence of CK19-positive cells in MCC [59, 62]. CK19 has been used as an epidermal stem cell marker [64], but is also present on mature Merkel cells [65]. Moreover, Abbas and Bhawan found no CK15-positive cells in MCC [62].…”
Section: Putative Cells Of Origin For MCCmentioning
confidence: 99%
“…Proliferation rate was examined with 5-bromodeoxyuridine (BrdU)-pulsed cultures as previously described [32]. Briefly, melanoma cells were plated onto AcOH or chitosan in culture medium containing 10 µM BrdU for 24h.…”
Section: Methodsmentioning
confidence: 99%